Protective effects of selenium against potassium dichromate-induced hematotoxicity in female and male Wistar albino rats - Ounassa Adjroud (Annales de Toxicologie Analytique, 2010)
Objective: Potassium dichromate (K2Cr2O7) is a potent pollutant for human and animal health. The purpose of the current work is to compare the effect of K2Cr2O7 using variations in the dose, route of administration and duration of exposure in male and female Wistar albino rats and to research the interaction of chromium and selenium with a special focus on hematopoiesis.  Materials and methods: K2Cr2O7 was subcutaneously administered alone (10, 50 and 100 mg/kg body weight) or K2Cr2O7 (10 mg/kg) in association with selenium (0.3 mg/kg) was administered to female Wistar albino rats. Male rats received in their drinking water K2Cr2O7 (30 mg/L/day) alone or in association with Se (0.3 mg/L/day) for 20 consecutive days. The hematological parameters were evaluated on days 3, 6 and 21 after subcutaneous (sc.) treatment in female rats and on days 10 and 20 after oral administration in male rats.  Results: K2Cr2O7− induced during the first three days a significant (p < 0.05) dose-dependent decrease in the number of erythrocytes, platelets, leucocytes, lymphocytes and the hematocrit levels, and a dose-dependent increase in the number of granulocytes and monocytes. In the drinking water, chromium sc. significantly decreased the number of leucocytes and lymphocytes on day 10 after treatment and elevated the number of granulocytes and monocytes 20 days later. Selenium sc. counterbalanced the hematotoxic effects of chromium in female rats.  Conclusion: These results suggest that the selenium has a protective role against the hematotoxicity of subcutaneous chromium in female Wistar rats.